2022
DOI: 10.1155/2022/2896895
|View full text |Cite
|
Sign up to set email alerts
|

Eryngium foetidum L. (Apiaceae): A Literature Review of Traditional Uses, Chemical Composition, and Pharmacological Activities

Abstract: Eryngiumfoetidum L. is popularly known as chicória-do-Pará, is native to the Amazon region, and is widely distributed in Northern Brazil. It is considered a versatile species due to its diversified uses in ethnomedicine, gastronomy, and pharmaceutical industry. The objective of this study was to review the literature on the traditional uses, chemical composition, and pharmacological activities of E. foetidum based on information published in national and international scientific articles between the years 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…The plants of the genus Eryngium have not been the exception; thus, the evaluation of the extracts of Eryngium spp. distributed around the world, have shown multiple beneficial effects [ 43 ], such as anti-inflammatory [ 44 ], against snake and scorpion venoms [ 45 , 46 ], antibacterial, antioxidant [ 47 ], antihyperglycemic [ 48 ], and cytotoxic against human tumor cell lines [ 49 ], among others.…”
Section: Biological and Pharmacological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The plants of the genus Eryngium have not been the exception; thus, the evaluation of the extracts of Eryngium spp. distributed around the world, have shown multiple beneficial effects [ 43 ], such as anti-inflammatory [ 44 ], against snake and scorpion venoms [ 45 , 46 ], antibacterial, antioxidant [ 47 ], antihyperglycemic [ 48 ], and cytotoxic against human tumor cell lines [ 49 ], among others.…”
Section: Biological and Pharmacological Activitymentioning
confidence: 99%
“…Additionally, it is important to point out that the study of the anticholelithiasis and trypanocidal activity shown by E. carlinae and E. heterophyllum , respectively, could extend to other species of Eryngium ; likewise, other activities such as anticlastogenic, anticarcinogenic, antihelmintic, and larvicidal, amongst others reported for E. foetidum could be evaluated [ 43 ].…”
Section: Biological and Pharmacological Activitymentioning
confidence: 99%
“…primarily due to the presence of polyphenols and saponins [212][213][214]. It has demonstrated potential for use in gastrointestinal diseases and exhibits antibacterial, analgesic, anthelmintic, anticonvulsant, and anticancer properties, highlighting its crucial importance in ethnopharmacology [215]. The aerial part of the plant collected during flowering is used for therapeutic purposes.…”
Section: Eryngium Planum L Seler Family -Apiaceaementioning
confidence: 99%
“…The plant’s aboveground parts are bioactive primarily due to the presence of polyphenols and saponins [ 136 , 137 , 138 , 139 , 140 ]. It has demonstrated potential for use in gastrointestinal diseases and exhibits antibacterial, analgesic, anthelmintic, anticonvulsant, and anticancer properties, thereby proving its crucial importance in ethnopharmacology [ 141 ]. The aerial part of the plant collected during flowering is used for therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%